Kontekstualisasi Pesan Lagu Al-Maḥkamaḥ Karya Kāẓim Al-Sāhir melalui Analisis Tindak Tutur Ilokusi - Adawiyah, Alfina Robi’ah; Rayana, Arum (Crises on Languages and Literature, 2026)
This study aims to describe the types of illocutionary speech acts in the song al-Maḥkamaḥ by Kāẓim al-Sāhir. This study will also discuss the messages listeners can take away from the song. It is hoped that the message will be useful to anyone currently living in a household or who will live in one. This research is a descriptive qualitative study. The data source for this study is the lyrics of the song al-Maḥkamaḥ by Kāẓim al-Sāhir, obtained directly from the YouTube account @rotanamusic. In collecting data, the listening and note-taking technique was used, with the following steps: listening to and understanding the song, noting the lyrics, identifying the data, and classifying the data. Meanwhile, in analyzing the data, there are several stages: reading, determining the type of illocutionary speech act, describing the illocutionary speech act in the lyrics of the song al-Maḥkamaḥ by Kāẓim al-Sāhir, revealing the message behind the lyrics, and concluding the analysis. In the song al-Maḥkamaḥ by Kāẓim al-Sāhir, 43 illocutionary speech acts were found, 5 of which were assertive illocutionary speech acts. In this study, 9 imperative, 8 commissive, 13 expressive, and 8 declarative speech acts were also identified. In previous studies, there has been no in-depth examination of the song's message. In this study, it can also be concluded that the main message for listeners of this song is caution in choosing a life partner.